(untitled) (Victoria Journal of Management, 2025)
In global era, business organizations corporate social responsibility (CSR) was still a lack of clarity on whether that initiative is expenses or investment for business. This research aims to analyze the influence and correlation between CSR efforts and the financial performance of publicly listed companies in Nepal. Descriptive and causal research design was applied to carry out this examination. For that, published annual and CSR reports were collected. The findings demonstrate that return on assets (ROA), net income (NI), and earnings per share (EPS) substantially validate the firm’s performance. It approves that the expenditure on CSR is set to prove an investment instead of a cost. This study may encourage equally firms’ executives to consider CSR as a business promotional tool rather than only responsibility towards stakeholders in general.